(untitled) (Olhar de Professor, 2021)
This investigation aims to understand, from the perspective of teachers linked to a teacher training course, the development of teaching activities through remote teaching. In this way, the research is characterized as an exploratory, descriptive case study with a qualitative approach, with teachers from a Biological Sciences degree course as participants. The data were collected through an online questionnaire and analyzed in a descriptive way, categorized and interpreted as recommended by Bardin (2011). The participants listed the diversity of didactic resources, flexibility of time and space of classes as benefits of remote teaching, however, the inability to use technological resources, the lack of institutional support, the difficulties in accessing equipment and the internet hamper effectiveness of this educational practice. In this way, teachers recognize the importance of educational technologies, however they are alert to the adversities that can increase inequality of access to education, particularly in this period of social distance.